Measurement of various morphometric parameters of the ulna and analyzing its variations will help in sex determination & can play important role in forensic science - Amarjyoti Chaturvedi, Dr.Pawan Kumar Mahato, Rajendra Singh, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Aim: In this work, we will examine a number of ulna morphometric features, look for genderdifferences in these parameters, and find that the measurements of male and female bones are significantly different.